The "Metallo"‐Diels–Alder Reactions: Examining the Metalloid Behavior of Germanimines. Issue 12 (21st February 2020) - Evans, Matthew J.; Anker, Mathew D.; Mouchfiq, Ahmed; Lein, Matthias; Fulton, J. Robin
Abstract: Addition of MesN3 (Mes=2, 4, 6‐Me3 C6 H2 ) to germylene [(NON t Bu )Ge] (NON t Bu =O(SiMe2 N t Bu)2 ) (1 ) gives germanimine, [(NON t Bu )Ge=NMes] (2 ). Compound 2 behaves as a metalloid, showing reactivity reminiscent of both transition metal‐imido complexes, undergoing [2+2] addition with heterocumulenes and protic sources, as well as an activated diene, undergoing a [4+2] cycloaddition, or "metallo"‐Diels–Alder, reaction. In the latter case, the diene includes the Ge=N bond and π‐system of the Mes substituent, which is reactive towards dienophiles including benzaldehyde, benzophenone, styrene, and phenylacetylene. Abstract : The metalloid behavior of germanimines is exhibited in their ability to behave as transition metal imido and organic imines. Both [2+2] and [4+2] cycloaddition is observed, the latter of which can be considered a "metallo"‐Diels–Alder reaction.